Prefrontal gray matter volume recovery in treatment‐seeking cocaine‐addicted individuals: a longitudinal study. (28th April 2016) - Parvaz, Muhammad A.; Moeller, Scott J.; d'Oleire Uquillas, Federico; Pflumm, Amanda; Maloney, Tom; Alia‐Klein, Nelly; Goldstein, Rita Z.
Abstract: Deficits in prefrontal cortical (PFC) function have been consistently reported in individuals with cocaine use disorders (iCUD), and have separately been shown to improve with longer‐term abstinence. However, it is less clear whether the PFC structural integrity possibly underlying these deficits is also modulated by sustained reduction in drug use in iCUD. Here, T1‐weighted magnetic resonance imaging scans were acquired, and performance on a neuropsychological test battery was assessed, in 19 initially abstinent treatment‐seeking iCUD, first at baseline and then after six months of significantly reduced or no drug use (follow‐up). A comparison cohort of 12 healthy controls was also scanned twice with a similar inter‐scan interval. The iCUD showed increased gray matter volume in the left inferior frontal gyrus and bilaterally in the ventromedial prefrontal cortex at follow‐up compared to baseline; healthy controls, as expected, showed no changes over this same time period. The iCUD also showed improved decision making and cognitive flexibility, with the latter correlated significantly with the gray matter volume increases in the inferior frontal gyrus. Given its association with improved cognitive function, the longitudinal recovery in cortical gray matter volume, particularly in regions where structure and function are adversely affected by chronic drug use, reflects a quantifiable positive impact of significantly reduced drug use on cortical structural integrity. Abstract : This study reports the longitudinal recovery in prefrontal cortical gray matter volume, particularly in regions that are adversely affected by chronic drug use, after 6months abstinence or reduction in cocaine use in treatment seeking individuals with chronic cocaine use. The study also reports longitudinal improvements in decision making and cognitive flexibility, with the latter correlated significantly with longitudinal increase in prefrontal gray matter volume. Results reflect a quantifiable positive impact of significantly reduced drug use on cortical structural integrity.